2017
DOI: 10.1016/j.contraception.2016.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of abortion-related near-miss complications in Zambia: cross-sectional study in Central, Copperbelt and Lusaka Provinces

Abstract: The abortion-related near-miss rate is high in Zambia compared with other restrictive contexts. Our results suggest that near-miss is a promising indicator of unsafe abortion; can be measured using routine hospital data, conveniently defined using the WHO criteria; and can be incorporated into the frequently utilized prospective morbidity methodology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 33 publications
1
35
1
Order By: Relevance
“…The abortion‐related near‐miss ratio in our study was much lower than reported in Zambia, likely accounted for by differences in near‐miss definition criteria. In the Zambian estimate, clinical and management‐based criteria were re‐defined and diagnostic thresholds for near‐miss were lowered compared with our study. The prevalence of maternal near miss associated with ectopic pregnancy was comparable with observations from Iran .…”
Section: Discussioncontrasting
confidence: 84%
“…The abortion‐related near‐miss ratio in our study was much lower than reported in Zambia, likely accounted for by differences in near‐miss definition criteria. In the Zambian estimate, clinical and management‐based criteria were re‐defined and diagnostic thresholds for near‐miss were lowered compared with our study. The prevalence of maternal near miss associated with ectopic pregnancy was comparable with observations from Iran .…”
Section: Discussioncontrasting
confidence: 84%
“…There were 0.9 and 2.1 severe abortion complications per 100 deliveries in Tanzania and Uganda, respectively. These values are similar to that of 1.5 per 100 live births reported in a study from Zambia . Studies that did not specifically include abortion as a screening event have reported lower rates; for example, another study in Uganda reported 39 abortion‐related near‐misses per 25 840 live births (0.16 per 100 deliveries) .…”
Section: Discussionsupporting
confidence: 81%
“…Studies that did not specifically include abortion as a screening event have reported lower rates; for example, another study in Uganda reported 39 abortion‐related near‐misses per 25 840 live births (0.16 per 100 deliveries) . Lowering the threshold of blood transfusion also increased the identification of abortion‐related near‐miss cases, an observation made by a previous study in Zambia …”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations